Ethanol ablation for ventricular arrhythmias: A systematic review and meta‐analysis. (5th January 2022) - Creta, Antonio; Earley, Mark J.; Schilling, Richard J.; Finlay, Malcolm; Sporton, Simon; Dhinoja, Mehul; Hunter, Ross J.; Papageorgiou, Nikolaos; Ang, Richard; Chow, Anthony; Lowe, Martin; Segal, Oliver R.; et al.
Abstract: Introduction: Ethanol ablation (EA) is an alternative option for subjects with ventricular arrhythmias (VAs) refractory to conventional medical and ablative treatment. However, data on the efficacy and safety of EA remain sparse. Methods: A systematic literature search was conducted. The primary outcomes were 1) freedom from the targeted VA and 2) freedom from any VAs post‐EA. Additional safety outcomes were also analyzed. Results: Ten studies were selected accounting for a population of 174 patients (62.3 ± 12.5 years, 94% male) undergoing 185 procedures. The overall acute success rate of EA was 72.4% (confidence interval [CI95% ]: 65.6–78.4). After a mean follow‐up of 11.3 ± 5.5 months, the incidence of relapse of the targeted VA was 24.4% (CI95% : 17.1–32.8), while any VAs post‐EA occurred in 41.3% (CI95% : 33.7–49.1). The overall incidence of procedural complications was 14.1% (CI95% : 9.8–19.8), with pericardial complications and complete atrioventricular block being the most frequent. An anterograde transarterial approach was associated with a higher rate of VA recurrences and complications compared to a retrograde transvenous route; however, differences in the baseline population characteristics and in the targeted ventricular areas should be accounted. Conclusion: EA is a valuable therapeutic option for VAs refractory to conventional treatment and can result in 1‐year freedom from VA recurrence in 60%–75% of the patients. However, anatomical or technical challenges preclude acute success in almost 30% of the candidates and the rate of complication is not insignificant, highlighting the importance of well‐informed patient selection. The certainty of the evidence is low, and further research is necessary.